Formulasi Strategi Pemasaran Sebagai Upaya Meningkatkan Penjualan Pada Masa Pandemi Di Hp Mart Kota Sampang - Sofia, Hikma; Surya Winata, Achmad Yahya (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
The problems identified in this study began with the declining level of sales as a result of the COVID-19 pandemic. This condition is contradictory, during the pandemic all activities are carried out online. Should require gadgets such as mobile phones to support daily activities. This study intends to design a marketing strategy formulation through a SWOT and AHP analysis approach. This is done so that marketing strategies can be found that can increase sales of HP Mart stores. Research resource persons were determined by purposive sampling related to the management of the Hp Mart business. The results of the SWOT analysis obtained the IFAS value of 2 while the EFAS value of 1,02. Thus, if drawn using a SWOT Analysis Diagram, HP Mart is in a very profitable situation. The result of choosing a competitive strategy using the Analytical Hierarchy Process (AHP) is to utilize its strengths, namely a strategic location, many HP Mart branches, a fairly complete cellphone and cellphone accessories store, good store security, good service to customers, as well as relationships with customers. good distributors to minimize the declining purchasing power of the people.